2011
DOI: 10.3892/etm.2011.292
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids decrease body weight and food intake and inhibit appetite regulatory peptide expression in the hypothalamus of rats

Abstract: Abstract. The aim of the present study was to investigate the effects of glucocorticoids (GCs) on appetite and gene expression of the hypothalamic appetite regulatory peptides, neuropeptide Y (NPY), agouti-related protein (AGRP) and cocaine and amphetamine-regulated transcript (CART), in non-obese and obese rats. Both non-obese and obese rats were randomly assigned to three groups: normal saline, low-and high-dose GC groups (NSG, LDG and HDG, respectively), which received an intraperitoneal injection with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 52 publications
2
30
0
2
Order By: Relevance
“…Dependent on the method and duration of corticosterone (Cort) administration, proopiomelanocortin ( Pomc ) expression has both increased (4, 5) and decreased (6) after treatment. Similarly agouti-related protein ( Agrp ) expression follows this inconsistency in response to Cort treatment (7, 8). Although the Gc-response elements (GREs) are present within the promotor regions of Agrp (9), Pomc (10), and neuropeptide Y ( Npy ) (11), the effect of chronic Gc treatment is still unclear.…”
mentioning
confidence: 99%
“…Dependent on the method and duration of corticosterone (Cort) administration, proopiomelanocortin ( Pomc ) expression has both increased (4, 5) and decreased (6) after treatment. Similarly agouti-related protein ( Agrp ) expression follows this inconsistency in response to Cort treatment (7, 8). Although the Gc-response elements (GREs) are present within the promotor regions of Agrp (9), Pomc (10), and neuropeptide Y ( Npy ) (11), the effect of chronic Gc treatment is still unclear.…”
mentioning
confidence: 99%
“…Circulating levels of glucocorticoids, either basal or stress-induced changes, have been shown to influence food choice, body weight and appetite in both humans and animals (Oliver and Wardle, 1999; Baran et al, 2009; Liu et al, 2011; Schwabe and Wolf, 2011) and this may be an important contributing factor to seasonal variation in food intake.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Animal studies in the laboratory have revealed that, overall, stress-induced changes in circulating glucocorticoids or exogenous administration of glucocorticoids (thereby elevating basal levels) leads to a decrease in food intake (Levine and Morley, 1981; Morley et al, 1983; Liu et al, 2011). In laboratory studies under free-feeding conditions, when rats were administered exogenous glucocorticoids over a period of days, mimicking a chronic elevation in basal levels of glucocorticoids as would be observed in SD, winter months, a decrease in food intake leading to a decrease in body weight was reported (De Vos et al, 1995; Liu et al, 2011).…”
Section: Glucocorticoidsmentioning
confidence: 99%
See 2 more Smart Citations